RANCANG BANGUN ALAT IRIGASI TETES BERBASIS WAKTU MENGGUNAKAN ALAT MIKROKONTROLER UNTUK MENINGKATKAN PERTUMBUHAN TANAMAN SAWI - Entengo, Reflin; Sukainah, Andi; Patang, Patang (Jurnal Pendidikan Teknologi Pertanian, 2019)
This study aims to design a time-based automatic control irrigation system that can minimize the use of water in plant cultivation, and can meet the needs (supply) of plants according to the water needed. This research uses research and development methods (R & D), the results are analyzed using quantitative data analysis and descriptive statistics, the The design of time-based drip irrigation equipment uses a microcontroller through several mechanisms including frame makingÂ  the installation of material components and the manufacture of microcontroller systems, the installation components and inputting language programs on microcontroller systems can be used effectively and efficiently if used by manual watering by humans.